SOSIALISASI EDUKASI ETIKA SEBAGAI LANDASAN MORALITAS PERILAKU REMAJA YANG BERKARAKTER DI DESA KWALA SIKASIM - Tutiariani Nasution; Atikah Rahmah Nasution; Bambang Gulyanto; Zulfahmi Firmansyah; Puan Mailani (Smart Education, 2025)
Abstract: The development of the times and technological advances have brought about major changes in the social behavior patterns of adolescents, especially in terms of ethics and morality. Many adolescents have begun to lose their way in understanding the values of politeness, responsibility, and empathy. Seeing this condition, students of the Thematic Real Work Lecture (KKNT) FKIP Universitas Asahan carried out a Socialization Ethics Education as the Foundation of Moral Behavior for Character-Building in Kwala Sikasim Village, Batu Bara District. This activity aimed to provide teenagers with an understanding of the importance of ethics and morality as the basis for forming a positive, moral, and responsible character. The activity was carried out using an educational approach in the form of observation, presentations, interactive discussions, and documentation. The results of the activity showed a significant increase in teenagers' understanding and awareness of ethics. Based on the evaluation, the level of understanding of ethical values increased from 40% to 90%, participant activity rose from 50% to 95%, and awareness of polite and empathetic behavior increased from 45% to 85%. These results prove that educational-interactive methods are effective in fostering moral awareness and positive character among adolescents. This activity is expected to become a sustainable character building model for the younger generation in the village, so that they can become ethical individuals with noble character who contribute positively to their social environment. Keywords: Education, Ethics, Morality, Character, Teenager Abstrak: Perkembangan zaman dan kemajuan teknologi telah membawa perubahan besar terhadap pola perilaku sosial remaja, terutama dalam hal etika dan moralitas. Banyak remaja yang mulai kehilangan arah dalam memahami nilai-nilai sopan santun, tanggung jawab, dan empati. Melihat kondisi tersebut, mahasiswa Kuliah Kerja Nyata Tematik (KKNT) FKIP Universitas Asahan melaksanakan kegiatan Sosialisasi Edukasi Etika sebagai Landasan Moralitas Perilaku Remaja yang Berkarakter di Desa Kwala Sikasim, Kabupaten Batu Bara. Kegiatan ini bertujuan untuk memberikan pemahaman kepada remaja mengenai pentingnya etika dan moralitas sebagai dasar pembentukan karakter yang positif, berakhlak, dan bertanggung jawab. Metode pelaksanaan kegiatan menggunakan pendekatan penyuluhan berupa observasi, presentasi, diskusi interaktif, serta dokumentasi. Hasil kegiatan menunjukkan peningkatan signifikan pada pemahaman dan kesadaran etika remaja. Berdasarkan evaluasi, tingkat pemahaman nilai etika meningkat dari 40% menjadi 90%, keaktifan peserta naik dari 50% menjadi 95%, dan kesadaran berperilaku sopan serta empatik meningkat dari 45% menjadi 85%. Hasil ini membuktikan bahwa metode edukatif-interaktif efektif dalam menumbuhkan kesadaran moral dan karakter positif di kalangan remaja. Kegiatan ini diharapkan dapat menjadi model pembinaan karakter yang berkelanjutan bagi generasi muda di desa, agar mampu menjadi pribadi yang beretika, berakhlak mulia, dan berkontribusi positif bagi lingkungan sosialnya. Kata Kunci: Edukasi, Etika, Moralitas, Karakter, Remaja